2014
DOI: 10.1186/1756-0500-7-386
|View full text |Cite
|
Sign up to set email alerts
|

Zinc and copper levels in low birth weight deliveries in Medani Hospital, Sudan

Abstract: BackgroundLow birth weight (LBW) is a worldwide health problem, especially in developing countries. We conducted a case–control study at Medani Hospital, Sudan. Cases were women who delivered a LBW (<2500 g) newborn and consecutive women who delivered a normal weight (>2500 g) newborn were controls. Questionnaires were used to collect clinical data. Zinc and copper levels were measured by an atomic absorption spectrophotometer.FindingsThe two groups (50 in each arm) were well matched in their basic characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 39 publications
(49 reference statements)
0
12
0
Order By: Relevance
“…Conversely, two other studies reported serum zinc to be 40–172 µg/L higher in women who gave birth to a LBW infant compared to those who gave birth to an appropriate weight infant [60,66]. A further four studies, also based on women from India, reported no association between circulating zinc levels and birthweight [62,63,64,69] and this was also reported in two studies of Turkish women [58,65]. However, univariate analysis and small sample size in these studies may not provide an accurate assessment of the effects of maternal circulating zinc and birthweight.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Conversely, two other studies reported serum zinc to be 40–172 µg/L higher in women who gave birth to a LBW infant compared to those who gave birth to an appropriate weight infant [60,66]. A further four studies, also based on women from India, reported no association between circulating zinc levels and birthweight [62,63,64,69] and this was also reported in two studies of Turkish women [58,65]. However, univariate analysis and small sample size in these studies may not provide an accurate assessment of the effects of maternal circulating zinc and birthweight.…”
Section: Resultsmentioning
confidence: 90%
“…The association between maternal circulating zinc and birthweight was assessed in 14 studies based on women where inadequate dietary zinc intake was predicted to affect ≥17% of the population [57,58,59,60,61,62,63,64,65,66,67,68,69], of which 7 reported a significant association (Table 1) [57,59,60,61,66,67,68]. All three of the studies based on women from Africa reported serum/plasma zinc on average 72–333 µg/L lower in women who gave birth to a LBW infant compared to those who gave birth to an appropriate weight infant [57,59,67].…”
Section: Resultsmentioning
confidence: 99%
“…A clinical trial reported that daily Zn supplementation in women with relatively low plasma Zn concentrations at 19 weeks gestation is associated with greater infant birth weights and head circumferences. 112 Conversely, studies using blood samples collected at birth or in late pregnancy have produced inconsistent results, with eight studies 78,114119 showing no association and three studies 120122 observing an increased risk between maternal serum Zn levels and risk of delivering LBW infants.…”
Section: Effects Of Environmental Exposures On Fetal and Childhoodmentioning
confidence: 99%
“…Studies have shown significant direct correlations between birth weight and maternal levels of zinc (Zn) and copper (Cu) in serum [21]. As for manganese (Mn), it has been suggested that Mn levels in maternal whole blood influence birth weight [22,23], while the absence of a correlation between birth weight and Mn, Cu, Zn and selenium (Se) in maternal blood has also been reported [24][25][26].…”
Section: Introductionmentioning
confidence: 98%